Well-posedness and exponential decay for a laminated beam with distributed delay term - Madani DOUIB, Madani DOUIB; ZITOUNI, Salah; Abdelhak DJEBABLA, Abdelhak DJEBABLA (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we study the well-posedness and the asymptotic behavior of a one-dimensional laminated beam system with a distributed delay term in the first equation, where the heat conduction is given by Fourier’s law effective in the rotation angle displacements. We first give the well-posedness of the system by using the semigroup method. Then, we show that the system is exponentially stable under the assumption of equal wave speeds. Mathematics Subject Classification (2010): 35B40, 35L56, 74F05, 93D20. Received 12 November 2019; Accepted 27 December 2019.